Glaciers of the Avachinskaya volcano group: current condition (state) - T. M. Manevich; Ya. D. Murav'ev; S. B. Samoilenko (Лëд и снег, 2015)
The present-day glaciation of the Avachinskaya volcano group was analyzed using data obtained during field works of 2007–2010. Twenty seven glaciers were found on the volcanic slopes with their total area of 24.04±3.6 km2. These glaciers belong to eight morphological types, the largest part of them are glaciers of slopes, cirques, and barrancoes. Great extent, diversity of climatic conditions and volcanic edifices made possible to group the glaciers into three glacial knots (complexes): the Avachinsky complex, the Koryaksky volcano, and the Pinachevsky Range, each one with own specific features. Comparison of recent data with aerial photographs of 1974 has allowed estimating changes of the glacier front positions and to reconstruct the glacier dynamics for the last 40 years. At the present time, seven glaciers advance, two ones degrade, and eighteen glaciers are in the stationary state.